Investigación de Mycobacterium avium subsp. paratuberculosis en leche ultrapasteurizada para consumo humano - Magnano, G.G. (2009)
Currently, Mycobacterium avium subsp. paratuberculosis is linked to Crohn's disease in humans as a potential etiologic agent. One route of infection to be considered is by the ingestion of contaminated milk. The objective of the present work was to evaluate Map's presence in commercial homogenized and ultrapasteurized milk for human consumption in supermarkets in the city of Río Cuarto, Córdoba, Argentina. Ninety eight packages of 1 liter of entire, homogenized and ultrapasteurized milk of six commercial brands were sampled. After decontamination by the modified Cornell's method, the samples were cultured in Herrol's medium with and without micobactin. All samples were negative. Possible causes of this result such as the origin of the milk and its probable very low amount of micobacterias, the efficiency of the pasteurization, the processing in the laboratory, among others are here discussed.